2017
DOI: 10.1021/acsnano.7b02777
|View full text |Cite
|
Sign up to set email alerts
|

Direct Laser Writing of δ- to α-Phase Transformation in Formamidinium Lead Iodide

Abstract: Organolead halide perovskites are increasingly considered for applications well beyond photovoltaics, for example, as the active regions within photonic devices. Herein, we report the direct laser writing (DLW: 458 nm cw-laser) of the formamidinium lead iodide (FAPbI3) yellow δ-phase into its high-temperature luminescent black α-phase, a remarkably easy and scalable approach that takes advantage of the material’s susceptibility to transition under ambient conditions. Through the DLW of α-FAPbI3 tracks on δ-FAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 63 publications
4
76
0
Order By: Relevance
“…This conversion typically occurs quickly, within 24 h . Surprisingly, it was reported that a more stable conversion to the α‐phase can be achieved by direct laser writing, with phase stability demonstrated over a period of four weeks . While the obtained results are interesting from the perspective of a fundamental understanding and possible uses for some specific applications requiring material patterning, large‐area devices such as solar cells require different methods for phase stabilization.…”
Section: Structure Of Fa‐based Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…This conversion typically occurs quickly, within 24 h . Surprisingly, it was reported that a more stable conversion to the α‐phase can be achieved by direct laser writing, with phase stability demonstrated over a period of four weeks . While the obtained results are interesting from the perspective of a fundamental understanding and possible uses for some specific applications requiring material patterning, large‐area devices such as solar cells require different methods for phase stabilization.…”
Section: Structure Of Fa‐based Perovskitesmentioning
confidence: 99%
“…[48] Annealing above 150-160 °C results in a reversible transition to the α-phase, but the crystals typically revert to the δ phase upon storage in an ambient environment. [39,48] This conversion typically occurs quickly, within 24 h. [46,47] Surprisingly, it was reported that a more stable conversion to the α-phase can be achieved by direct laser writing, with phase stability demonstrated over a period of four weeks. [39] Small Methods 2018, 2, 1700387 [8,14] a-c) Reproduced with permission.…”
Section: Crystalline Structurementioning
confidence: 99%
“…High‐efficiency PSCs have been mostly prepared in an oxygen‐ and moisture‐free glove‐box atmosphere . However, processes requiring a sub‐ppm H 2 O content surely represent a restriction to the industrialization of PSCs, especially when it is considered that there is a lack of effective solutions to this problem until now …”
Section: Promising Hole Transporter Materials (Htms) Alternatives To mentioning
confidence: 99%
“…[107][108][109][110] However, processes requiring as ub-ppm H 2 Oc ontent surely represent ar estriction to the industrialization of PSCs, especially when it is considered that there is al ack of effective solutionst ot his problem until now. [29,[111][112][113] Among the attempts to address this issue, Taie tal. reported the use of aP b(SCN) 2 precursor in preparingP SCs in ambient air,o btaining high-quality CH 3 NH 3 PbI 3Àx (SCN) x films even when the relative humidity exceeded 70 % [114] ( Figure 5AB).…”
Section: Emergent Substrates:from Ito/fto-free Devices To Flexible Armentioning
confidence: 99%
See 1 more Smart Citation